Liberal Moments Reading Liberal Texts - Atanassow, Ewa; Kahan, Alan S. (Textual Moments in the History of Political Thought, 2017)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Liberalism today has perhaps more supporters and adversaries than any other political movement. This volume traces liberalism's global ascent through essays about some of the thinkers and actors who participated in its rise and spread. The essays included here present for the first time in one place the geographic and ideological diversity of liberal thought and practice as it developed since the eighteenth century. By exploring thinkers as diverse as Montesquieu, Abraham Lincoln, Jacob Burckhardt, Khayr al-Din, Hu Shih, John Rawls, and Czeslaw Milosz, this volume contributes toward a better understanding of liberalisms past and present. Each chapter opens with a critical passage from the author under consideration and explores the author's significance for liberalism. By facilitating a direct encounter with influential authors and texts, the volume serves as an introduction both to the multiple dimensions of liberalism and to reading texts in political thought. By engaging with particular liberal moments, the essays allow readers to create and explore conversations among liberalisms across time and space. It thus encourages a broader and more nuanced understanding of the nature and history of liberalism. Stimulating, accessible and interdisciplinary, Liberal Moments will appeal to students and scholars in the history of political thought, intellectual history and beyond.